Application of Cement-Based Composite Nanomaterials in Prefabricated Thin-Wall Light Steel Structure Composite Wall - Xiaoxu Chen; Huatuo He; Lingzhao Huo; Zhaorong Chen (International Journal of Analytical Chemistry)
In order to solve the problem of seismic performance of prefabricated concrete shear walls connected with ultra-high performance cement-based composite (UHPC) after short lap of steel bars, the author proposes a cement-based composite nanomaterial in the prefabricated thin-walled lightweight application in steel structure composite wall. In order to explore the influence of the axial compression ratio on its seismic performance, 1 is a cast-in-place shear wall with a design axial compression ratio of 0.2, and 3 is a prefabricated shear wall with a design axial compression ratio of 0.2, 0.33, and 0.47, respectively, all the specimens were mainly damaged by shear compression. The test results show that the cracking loads of specimens PW2 and PW3 are increased by 17.04% and 38.81%, respectively, the yield load is increased by 27.74% and 50.28%, respectively, and the peak load is increased by 25.29% and 48.4%, respectively. Conclusion. With the increase of the axial compression ratio, the crack resistance and bearing capacity of the specimens are significantly improved.